Analysis Of The Use Of Return On Asset, Return On Equity, And Economic Value Added In Assessing Company Financial Performance - Nurjanah, Yayuk; Prasetyo, Disva Margaretha (Institut Bisnis dan Informatika Kesatuan, 2024)
The purpose of this study was to determine the financial performance of PT Unilever Indonesia Tbk., PT Gudang Garam Tbk., and PT Bank Central Asia Tbk. in 2019, 2020 and 2021 using ROA, ROE and EVA analysis. The results of this study indicate that PT Unilever's financial performance in terms of ROA, ROE, and EVA shows unfavorable results. This is because PT Unilever's ROA, ROE, and EVA tend to decrease from year to year. This decline was mainly due to decreasing profits during the Covid-19 pandemic in 2020 and PT Unilever has not been able to fully recover from the decline during this pandemic. The overall financial performance of PT Gudang Garam is not good because most of PT Gudang Garam's ROA, ROE, and EVA values ​​show a decline. However, PT Gudang Garam is trying to improve its performance in 2021, one of which is by reducing its capital costs. Then, PT Bank Central Asia's financial performance showed good results because ROA, ROE, and EVA managed to increase in 2021 after experiencing a slight decline in 2020. In addition, PT Bank Central Asia's total equity and total assets also increased from 2019 until 2021 which may indicate that the financial condition of PT Bank Central Asia is in a fairly stable position Keywords : ROA, ROE, EVA